2019
DOI: 10.12998/wjcc.v7.i17.2630
|View full text |Cite
|
Sign up to set email alerts
|

Wilson disease associated with immune thrombocytopenia: A case report and review of the literature

Abstract: BACKGROUNDWilson disease (WD) is a genetic disorder of hepatic copper excretion, leading to copper accumulation in various tissues. The manifestations are quite variable, and hemolytic anemia is the most common hematological presentation. WD associated with thrombocytopenia is very rare.CASE SUMMARYWe report the case of an 11-year-old Chinese girl with WD that was associated with immune thrombocytopenia (ITP). Thrombocytopenia was the initial chief complaint for her to visit a hematologist, and ITP was diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(25 reference statements)
0
1
0
1
Order By: Relevance
“…Thrombocytopenia with negative antiplatelet antibodies has been reported in children, attributed to hypersplenism and/or D-penicillamine therapy’s side-effects [ 22 ]. A few studies have indicated idiopathic thrombocytopenia as an initial sign in patients with WD [ 23 , 24 ]. Our patient presented with thrombocytopenia, macroplatelets, and Döhle-like cytoplasmic inclusions in the megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia with negative antiplatelet antibodies has been reported in children, attributed to hypersplenism and/or D-penicillamine therapy’s side-effects [ 22 ]. A few studies have indicated idiopathic thrombocytopenia as an initial sign in patients with WD [ 23 , 24 ]. Our patient presented with thrombocytopenia, macroplatelets, and Döhle-like cytoplasmic inclusions in the megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin toxicity on basal ganglia is, in fact, well known 4,10 . Tremor is a feature of Wilson's Disease (WD), 7 which is characterized by liver dysfunction and hemolytic anemia 7 and can be associated with thrombocytopenia, 8 caused by the accumulation of copper. In addition, Bilirubin levels are increased in PD patients, 6 especially in tremor‐dominant ones, 5 and this could be due to the antioxidative properties bilirubin has in substantia nigra 6 …”
Section: Discussionmentioning
confidence: 99%
“…Дані літератури свідчать, що до пубертатного віку ХВ найчастіше характе ризується ураженням печінки або проявами гемолізу [7]. Для гемолітичних проявів у дітей більш характерною є Кумбс негативна гемолі тична анемія, водночас імунна тромбоцитопе нія притаманна дорослим [16]. Гепатоце люлярна карцинома та внутрішньопечінкова холангіокарцинома у хворих із ХВ зустріча ється з частотою 1,2% [11].…”
unclassified